Engineering students' strategies to learn programming correlate with motivation and gender - Weurlander, Maria; von Hausswolff, Kristina (Proceedings - Frontiers in Education Conference, 2021)
This full research paper reports on a study where we investigated engineering students' learning to program. In particular, we explored differences in students' strategies, how they work in the computer lab, and if this is related to their motivation, gender and overall tendency to engage in thinking. We gathered survey data from first year engineering students in an introductory, compulsory programming course. The survey consisted of established instruments and items constructed by us. 67 students answered the survey (response rate of 43 %). 18 % of the students that answered the survey did not have previous experiences of programming, and 43% were female. An exploratory factor analysis of the items relating to how students learn programming revealed three factors: 1) the individual thinker, 2) the social reader, and 3) the interactive problem-solver. We found gender differences relating to the second factor; female students reported more frequent use of the social reader strategy. There were also differences in reported used strategies and how students worked in the lab, previous experiences, need for cognition and motivation. These differences indicate that the factors individual thinker and interactive problem-solver were privileged in this programming course. Further research is needed to explore these findings in different educational contexts.